IMPROVING GOOD SOE CORPORATE GOVERNANCE THROUGH THE ROLE OF INDEPENDENT COMMISSIONERS - Muhammad Muchlas Rowi; Nurul Wahdah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
Through the Decree of the Minister of State for State-Owned Enterprises (BUMN) No. Kep-117/M-MBU/2002 concerning the Implementation of Good Corporate Governance (GCG) Practices in BUMN, BUMN is obliged to implement GCG principles. The GCG principles required by this decision include the principles of transparency, independence, accountability, liability and the principle of fairness. The problem formulation in this research is (1) What is the role of independent commissioners in BUMN in the context of improving good corporate governance? (2) How are the powers, functions and responsibilities of independent commissioners in BUMN regulated in the context of improving good corporate governance? (3) What is the concept of the role of independent commissioners in BUMN in the context of good company improvement? This type of research is normative juridical legal research, which is a process of discovering legal rules, legal principles and legal doctrines in order to answer the legal issues faced. The legal basis for state financial companies is that if Persero Negara currently in Indonesia suffers losses in its business transactions, Law Number 19 of 2003 concerning Entities is considered to be a state los. By State-Owned Enterprises, Article 1 paragraph (1) states that because the person in charge of managing the Persero is the State-Owned Enterprise, which is in the hands of the Board of Directors, it is the Board of Directors as the party hereinafter referred to as BUMN, that is the Business Entity that must be responsible. Therefore, all provisions and principles that apply to limited liability companies apply to companies as regulated in Law No. 40 of 2007 concerning Limited Liability Companies. It is recommended that one of the important issues that has emerged in the discourse on implementing good corporate governance is the formation of an Independent